Rancang Bangun Alat Peraga Sistem Kelistrikan Sepeda Motor Untuk Keperluan Praktikum TBSM SMK3 Negeri Bengkalis - Reinaldi Teguh Setyawan; Sunarto; Siti Umira; Irwan Kurniawan, Irwan Kurniawan (TANJAK : Jurnal Pengabdian Kepada Masyarakat, 2025)
The limited availability of electrical training media in motorcycle vocational schools leads to theoretical learning and reduces students’ hands-on experience. This community service project aimed to design, construct, and implement a motorcycle electrical trainer for the Department of Motorcycle Engineering and Business (TBSM) at SMK Negeri 3 Bengkalis. The trainer integrates four main subsystems: lighting, charging, ignition, and electric starter, assembled on a safe and ergonomic educational panel. The method consisted of needs analysis, design, component selection, fabrication, functional testing, module development, and classroom implementation with teacher–student mentoring. Functional tests showed that all subsystems operated according to the design, including protection through fuses and accessible measuring points. Classroom use received positive responses; the trainer was considered relevant to the curriculum and helped students understand circuit flow, perform voltage measurements, and practice basic fault diagnosis. The activity produced a trainer unit, practicum modules, and opportunities for scientific publications and intellectual property.